A COMPARATIVE STUDY TO EVALUATE THE SERUM LIPID LEVELS AND LIPOPROTEIN-(a) WITH PREGNANCY INDUCED HYPERTENSION AND NORMOTENSIVE PREGNANT WOMEN AT A TERTIARY CARE TEACHING HOSPITAL IN TELANGANA. - Deepa Polepaka; Narender Sayini; J. Naveena (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background and objectives: Blood pressure of 140/90 mm Hg or higher, without proteinuria and oedema after 20 weeks of pregnancy, is considered pregnancy-induced hypertension. A clinical characteristic of PIH, proteinuria and hypertension, can arise from endothelial dysfunction associated with dyslipidaemias. There is a clear correlation between the rise in plasma triglycerides and plasma cholesterol and the steady increase in mean serum oestradiol concentration from 10 to 35 weeks of pregnancy. Serum lipid concentration and serum Lipoprotein (a) levels may provide a useful marker for screening patients at risk for developing PIH. Therefore, the study aims to assess and compare the serum levels of lipid and lipoprotein (a) in pregnant women with pregnancy-induced hypertension and normotensive pregnant women.Methods: A case-control observational study was carried out at the Government General Hospital, Karimnagar, over 12 months with 50 cases of Pregnancy-induced hypertension and 50 age-matched controls.Results: A total of 100 subjects were grouped into cases and controls. Their serum lipid profile and lipoprotein (a) levels were evaluated. The t-test was used as a test of significance for qualitative data. A p-value of